BYSL contributes to tumor growth by cooperating with the mTORC2 complex in gliomas - Gao, Shangfeng (Cancer Biol Med, 2021)
OBJECTIVE: BYSL, which encodes the Bystin protein in humans, is upregulated in reactive astrocytes following brain damage and/or inflammation. We aimed to determine the role and mechanism of BYSL in glioma cell growth and survival. METHODS: BYSL expression in glioma tissues was measured by quantitative real-time PCR, Western blot, and immunohistochemistry. In vitro assays were performed to assess the role of BYSL in cell proliferation and apoptosis. Protein interactions and co-localization were determined by co-immunoprecipitation and double immunofluorescence. The expression and activity of the AKT/mTOR signaling molecules were determined by Western blot analysis, and the role of BYSL in glioma growth was confirmed in an orthotopic xenograft model. RESULTS: The BYSL mRNA and protein levels were elevated in glioma tissues. Silencing BYSL inhibited glioma cell proliferation, impeded cell cycle progression, and induced apoptosis, whereas overexpressing BYSL protein led to the opposite effects. We identified a complex consisting of BYSL, RIOK2, and mTOR, and observed co-localization and positive correlations between BYSL and RIOK2 in glioma cells and tissues. Overexpressing BYSL or RIOK2 increased the expression and activity of AKT/mTOR signaling molecules, whereas downregulation of BYSL or RIOK2 decreased the activity of AKT/mTOR signaling molecules. Silencing BYSL or RIOK2 decreased the growth of the tumors and prolonged the lifespan of the animals in an orthotopic xenograft model. CONCLUSIONS: High expression of BYSL in gliomas promoted tumor cell growth and survival both in vitro and in vivo. These effects could be attributed to the association of BYSL with RIOK2 and mTOR, and the subsequent activation of AKT signaling.